SurfaceConstellations: A Modular Hardware Platform for Ad-Hoc Reconfigurable Cross-Device Workspaces - Marquardt, Nicolai; Brudy, Frederik; Liu, Can; Bengler, Ben; Holz, Christian (Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems, 2018)
We contribute SurfaceConstellations, a modular hardware platform for linking multiple mobile devices to easily create novel cross-device workspace environments. Our platform combines the advantages of multi-monitor workspaces and multi-surface environments with the flexibility and extensibility of more recent cross-device setups. The SurfaceConstellations platform includes a comprehensive library of 3D-printed link modules to connect and arrange tablets into new workspaces, several strategies for designing setups, and a visual configuration tool for automatically generating link modules. We contribute a detailed design space of cross-device workspaces, a technique for capacitive links between tablets for automatic recognition of connected devices, designs of flexible joint connections, detailed explanations of the physical design of 3D printed brackets and support structures, and the design of a web-based tool for creating new SurfaceConstellation setups.